2001
DOI: 10.1111/j.1600-0684.2001.300104.x
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative analysis of natural killer cell activity, lymphoproliferation and lymphocyte surface antigen expression in nonhuman primates housed at the CIRMF Primate Center, Gabon

Abstract: Six different species of nonhuman primates housed at the CIRMF Primate Center, cynomolgus monkeys (Macaca fascicularis), rhesus monkeys (Macaca mulatta), mandrills (Mandrillus sphinx), vervets (Cercopithecus aethiops pygerythrus), chimpanzees (Pan troglodyte) and baboons (Papio hamadryas), were evaluated for their natural killer cell activity and for the ability of their peripheral blood mononuclear cells to proliferate in response to known mitogens (concanavalin A, phytohemagglutinin and staphylococcal entero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…In contrast, CD161/CD3-cells were associated with high levels of killing of K562 cells, which suggests that this phenotype likely contained M. nemestrina NK cells. In M. mulata (rhesus), CD56 has been reported to have [Poaty-Mavoungou et al, 2001] and not have [Carter et al, 1999] cytolytic killing function against K562 cells To test the relationship between CD56 expression and killing of K562 cells, we sorted cells into CD16-/ CD561 and CD161/CD3-/CD56-populations. The CD16-/CD561 population was associated with low K562 killing, while the CD161/CD3-/CD56-cells produced the highest K562 killing (Fig.…”
Section: K562 Killing From Fresh Peripheral Blood and Peripheral Bloomentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, CD161/CD3-cells were associated with high levels of killing of K562 cells, which suggests that this phenotype likely contained M. nemestrina NK cells. In M. mulata (rhesus), CD56 has been reported to have [Poaty-Mavoungou et al, 2001] and not have [Carter et al, 1999] cytolytic killing function against K562 cells To test the relationship between CD56 expression and killing of K562 cells, we sorted cells into CD16-/ CD561 and CD161/CD3-/CD56-populations. The CD16-/CD561 population was associated with low K562 killing, while the CD161/CD3-/CD56-cells produced the highest K562 killing (Fig.…”
Section: K562 Killing From Fresh Peripheral Blood and Peripheral Bloomentioning
confidence: 99%
“…[ Mingari et al, 1995]. We made an initial assumption that CD16 (FcgRIII) would be present on NK from M. nemestrina based on the fact that NK cells from humans [Colucci et al, 2002;Moretta et al, 2001Moretta et al, , 2002b, M. mulata [Carter et al, 1999;Poaty-Mavoungou et al, 2001], and cynomologus monkeys [Yamada et al, 1989] all express CD16, and that CD16 expression would be required for antibody-dependent cell-mediated cytotoxicity (ADCC). CD16 is present on a variety of cell types and is not a unique marker for NK cells.…”
Section: Killing Of K562 Cells From Culture Expanded Nk Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated several key phenotypic differences between peripheral blood T and natural killer cell subsets in humans and cynomolgus monkey. For example, in contrast to humans, cynomolgus monkeys have (a) a substantial population of CD4/CD8 double‐positive T cells (2); (b) a lower CD4 + :CD8 + T‐cell ratio (3); (c) CD90 + lymphocytes (1); and (d) CD56 + monocytes and CD56 − natural killer cells (1). The differences between cynomolgus monkey and human B cells are not completely understood.…”
mentioning
confidence: 99%
“…The identification of CD56 on NHP PBMC is more controversial. CD56 has been identified on peripheral blood cells of a number of non‐human primate species [27,30,34]. However, the levels of expression of CD56 and the characterization of CD56 + cells as NK cells with cytolytic activity are not consistent among the studies that have been reported.…”
Section: Introductionmentioning
confidence: 99%